Management of Lymphoedema by Varma Therapy: A Case Study - Anpuchelvi, S.; Sritharan, G.; Ganesan, S. (University of Colombo, Sri Lanka, 2022)
Varmam is the flow of vital energy in the body. Energy junctions in the body are called Varma points. Proper vibration or turning of the vital points (Varmam) by experts promotes health. These are very important vital places and any injury to these parts may lead to complications. In this case study, 22 years old female patient with lymphoedema and pain in both legs was selected. Finally identifying the Varma points and Varma stimulation therapy was done three times daily for 14 days and heated Thalankai oil-soaked cotton was applied over stimulated regions. 5th-day Patthu application and 13th-day, Suddigai (Agni) karma therapy were done on Varma points. After fourteen days the patient shows relief from the symptoms she suffered. This case study can be considered evidence of Varma therapy for lymphoedema. This can be explained by the concept of Varma stimulation on Varma points which leads stimulation to the endocrine system Anagatham (Thymus gland) and activate the Lymphatic channels. Lymphedema occurs when the lymph system is damaged or blocked. Fluid builds up in soft body tissue and causes swelling. So Anagatha chakra activates the Lymphatic channels and that effect plays a direct part in lymphoedema. The most important outcome of the study is relieving the symptoms and there is no recurrence within the study duration, as well as the follow-up, was done every month for more than eighteen months. Hence this study has a positive outcome and can be recommended as the therapeutic procedure for Lymphoedema
Keywords: Varma; Marma; Thalankai Oil; Anagatha chakra; Lymphoedema